Detailed Sensitivity Analysis of Reverse Osmosis Systems - Yahya, H.; Shaaban, S. (Journal of Advanced Research in Applied Mechanics, 2020)
The Reverse osmosis (RO) technique is considered the most promising technique for brackish water and seawater desalination. However, its power consumption is considerably higher than all other techniques. Therefore, the present study focuses on the performance of reverse osmosis plants in hot climate conditions. A typical Reverse osmosis system was designed, constructed and investigated. The ROSA software was also used for the analysis of seven different membrane elements. The experimental data were used in order to validate the simulation results of the ROSA software. A variance-based sensitivity analysis was performed in order to define the most effective operating parameters. The present investigation shows that the tap and brackish water membrane elements are more sensitive to the feed temperature rather than the feed pressure and concentration. Meanwhile, seawater membrane elements are more affected by the feed concentration. The detailed investigation of the different membrane elements shows that wastewater reclamation using reverse osmosis technology could be a significant source of low-cost fresh water for hot climate countries.